Online Belief Elicitation Methods - Valeria Burdea; Jonathan Woon (Center for Economic Studies and Ifo Institute (CESifo), 2021)
We evaluate the quality of beliefs elicited from online respondents, comparing several characteristics of two widely used elicitation mechanisms (the Binarized Scoring Rule - BSR - and a stochastic variation of the Becker-deGroot-Marshak mechanism -BDM) against a flat fee baseline for a variety of beliefs (induced probabilities, first-order factual knowledge, second-order knowledge of others). We find the flat-fee method is the most time-efficient, the BDM is the most difficult to understand, and there are no differences in the average accuracy of induced beliefs across conditions. However, the methods are significantly different in terms of the frequency of first-order and second-order beliefs reported at exactly 50%: the flat-fee method leads to the most mass on this belief, followed by BDM and BSR. We also find that incentives increase accuracy for less-educated participants, and that attention, numeracy, and education are positively associated with the quality of induced beliefs across methods. Our results suggest that the quality of beliefs elicited in online environments may depend less on the formal incentive compatibility properties of the elicitation procedure (whether the procedure prevents “dishonest” reporting) than on the difficulty of comprehending the task and how well incentives induce cognitive effort (thereby inducing subjects to quantify or construct their beliefs).
Keywords: C81; C89; D83; D91; 330; belief elicitation; incentives; online experiment